2013
DOI: 10.3767/003158513x669030
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the genus <I>Alternariaster</I> (<I>Dothideomycetes</I>)

Abstract: Alternariaster was erected in 2007 to accommodate Alternaria helianthi, a fungal species known to cause leaf spots on Helianthus annuus (sunflower). It was segregated from Alternaria based on conidial morphology. Recently an unknown alternaria-like dematiaceous fungus was found associated with leaf spots on Bidens sulphurea (yellow cosmos) in Brazil. Based on a multi-gene phylogeny of parts of the ITS and LSU genes, this fungus was placed within the Leptosphaeriaceae with Alternariaster helianthi as its closes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Our study showed that this genus is clearly not part of the Alternaria complex and belongs to the Leptosphaeriaceae (Fig. 2) (Alves et al 2013). …”
Section: Discussionmentioning
confidence: 80%
“…Our study showed that this genus is clearly not part of the Alternaria complex and belongs to the Leptosphaeriaceae (Fig. 2) (Alves et al 2013). …”
Section: Discussionmentioning
confidence: 80%
“…Further studies are needed to examine the life cycle of O. foeniculi and to ascertain the cardinal temperatures of the fungus for successful infection since this pathogen is well established in this representative fennel production area. This information is required for the setup and timing of sustainable approaches for soil disinfection, including solarization and/or fumigation at low rates, to reduce the level of the primary inoculum in the soil and hence the disease amount, like successfully applied for other soilborne plant pathogens (Vitale et al 2013;Aiello et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Simmons. Simmons (2007) considered Alternariaster to be related to Alternaria , however, Alves et al (2013) and Woudenberg et al (2013) clealy showed Alternariaster ( Leptosphaeriaceae ) to have a distinct phylogenetic affinity in Pleosporales and removed it from Alternaria sensu stricto ( Pleosporaceae ).…”
Section: Notes On Recent Changes and Namingmentioning
confidence: 99%